Century 87 . : Kunst van nu ontmoet Amsterdams verleden. - Balk, J. Th.; Ellenbroek, Willem; Ex, Sjarel; Gast, Nicolette; Hoek, Els; Shaffer, Wendie (Amsterdam : Stichting Onafhankelijk Kunsthistorisch Onderzoek, 1987)
Anselmo, Giovanni ; Baren, Peter ; Boltanski, Christian ; Byars, James Lee ; Clemente, Francesco ; Daniels, René ; van den Dobbelsteen, Jan ; Dokoupil, Jiri Georg ; Dujourie, Lili ; Flanagan, Barry ; van Golden, Daan ; De Groot, Kees ; van der Heyden, J.C.J. ; Holzer, Jenny ; Kemps, Niek ; van Koningsbruggen, Rob ; Laib, Wolfgang ; Mach, David ; Mol, Laurens Pieter ; Nolte, Titus ; Paik, Nam June ; de Pavert, Jan van ; Sarkis ; Scholte, Rob ; Struycken, Peter ; Tremlett, David ; Uglow, Alan ; de Zeeuw, Mirjam ; Zwillinger, Rhonda
* Zie speciale kast: cataloog met 4 viewmaster schijfjes
Nederlands & Engels
Century 87 - Kunst van nu ontmoet Amsterdams verleden, Amsterdam, 07.08 - 14.09.1987
boek
Keywords: Amsterdam